2014
DOI: 10.1021/ie4039532
|View full text |Cite
|
Sign up to set email alerts
|

HZSM-5 Zeolites with Different SiO2/Al2O3Ratios. Characterization and NH3Desorption Kinetics

Abstract: This article reports the influence of the SiO2/Al2O3 ratio (30, 80, and 280) on HZSM-5 zeolite properties. XRD patterns show a decrease in the XRD peak intensity at low 2θ angles for low SiO2/Al2O3 ratio zeolites. N2 adsorption and desorption isotherms display hysteresis with both micropores and mesopores likely contributing to the particles network. The NLDFT cylindrical model confirms the characteristic 5.5 Å micropores in the zeolite pore framework. Furthermore, specific surface area, pore volume, and pore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
129
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(157 citation statements)
references
References 87 publications
14
129
0
5
Order By: Relevance
“…This is in agreement with earlier studies that showed an increasing trend of zeolite acidity with Al/Si ratio [36][37][38]. It is seen that even the ammonium form of zeolites possess reasonable surface acidities without conversion to hydrogen forms.…”
Section: Characterization Of Zeolitessupporting
confidence: 93%
“…This is in agreement with earlier studies that showed an increasing trend of zeolite acidity with Al/Si ratio [36][37][38]. It is seen that even the ammonium form of zeolites possess reasonable surface acidities without conversion to hydrogen forms.…”
Section: Characterization Of Zeolitessupporting
confidence: 93%
“…4, in which the original diffraction intensity of FeZ has been reduced by 60 % for readier comparison. Peaks at 2h = 7.87°, 8.85°, and 23.07°appeared for FeZ; these positions are similar to those reported for as-synthesized H-ZSM-5 zeolite [27], indicating that all Fe ions are atomically isolated at extraframework sites. A sample of VWT gave strong reflection at 2h = 25.26°with substantial weak ones at higher 2h values.…”
Section: Major Role Of Fez In Suppression Of N 2 O Formationsupporting
confidence: 82%
“…The temperature of maximum desorption-cracking of t-BA (T TBA ) is linked to the acid strength of the catalyst, as stronger acid sites are active for the cracking of t-BA at lower temperatures. Considering this, the lower the temperature of the peak (lower T TBA ), the higher the acid strength of the sites, which is the opposite effect to that observed in the TPD analysis of commonly used NH 3 [6]. Besides, a small fraction of t-BA (signal at m/z = 58) is desorbed without cracking, corresponding to the base physisorbed on weak acid sites, which are inactive for the cracking of t-BA, and consequently also for the reactions involved in the transformation of 1-butene [25,45].…”
Section: Catalyst Characterizationmentioning
confidence: 85%
“…Rahimi and Karimzadeh [4] have reviewed the main modifications of MFI zeolites for obtaining and intensifying light olefin production, since the structure and acidity of the MFI zeolite could be tuned for each specific application by properly selecting the SiO 2 /Al 2 O 3 ratio [5][6][7], calcination with different protocols [8], using vapor at high temperatures namely steaming [9,10], incorporating rare earth or transition metals [4,11,12], protons by cations like Na + [13], selecting a proper matrix of binders and fillers [14], and by treatment with acids or bases [15,16], among others.…”
Section: Introductionmentioning
confidence: 99%